2021
DOI: 10.1155/2021/5510290
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pharmacological Mechanism of Duhuo Jisheng Decoction in Treating Osteoporosis Based on Network Pharmacology

Abstract: Objective. The purpose of this work is to study the mechanism of action of Duhuo Jisheng Decoction (DHJSD) in the treatment of osteoporosis based on the methods of bioinformatics and network pharmacology. Methods. In this study, the active compounds of each medicinal ingredient of DHJSD and their corresponding targets were obtained from TCMSP database. Osteoporosis was treated as search query in GeneCards, MalaCards, DisGeNET, Therapeutic Target Database (TTD), Comparative Toxicogenomics Database (CTD), and OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Here, we found that quercetin has been used as an agent for OP by reducing EGFR, HIF1A, and IL6 expression. EGFR, HIF1A, and IL6 have also been demonstrated as the therapeutic targets of OP ( Fayed et al, 2019 ; Luo et al, 2021 ; Xiong et al, 2021 ). Nobiletin, a polymethoxylated flavone, exhibits anti-oxidative, anti-inflammatory, and anti-cancer properties ( Murakami et al, 2000 ; Hagenlocher et al, 2019 ; Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that quercetin has been used as an agent for OP by reducing EGFR, HIF1A, and IL6 expression. EGFR, HIF1A, and IL6 have also been demonstrated as the therapeutic targets of OP ( Fayed et al, 2019 ; Luo et al, 2021 ; Xiong et al, 2021 ). Nobiletin, a polymethoxylated flavone, exhibits anti-oxidative, anti-inflammatory, and anti-cancer properties ( Murakami et al, 2000 ; Hagenlocher et al, 2019 ; Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included the following: (1) the study lacked a control group that met the inclusion criteria; (2) the animal model was a mouse, rabbit, or other experimental animals; (3) the osteoporosis model was not established by ovariectomy; (4) the data related to outcome measurements could not be extracted; (5) the study type was a review, conference abstract, commentary, case report, or letter; and (6) all studies that did not meet the inclusion criteria.…”
Section: Study Screeningmentioning
confidence: 99%
“…Because osteoporosis is usually an imbalance of bone resorption and bone formation caused by estrogen deficiency or aging, certain pharmacological agents, such as those that promote bone formation (parathyroid hormone) and those that inhibit osteoclast resorption (bisphosphonates), are widely used in the treatment of osteoporosis [4]. However, with the widespread clinical use of these drugs, adverse side effects have also been observed, such as drug-related osteonecrosis of the jaw [5]. Therefore, the search for new osteoporosis treatment strategies is of great clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…The Ginseng and Astragalus decoction (GAD) are composed of Astragalus and Ginseng to strengthen qi and help yang [ 8 ]. Astragalus and Ginseng are the top medicines described in the Shennong Materia Medica; they taste sweet and have the effect of tonifying qi [ 9 ]. In the “Elbow Reserve Urgent Prescription” written by Gehong in the Eastern Jin Dynasty, records of Ginseng and Astragalus were shared and then they subsequently appeared in the classic prescriptions for treating abnormal water metabolism, such as Baoyuan Decoction, Buzhong Yiqi Decoction, and Guipi Decoction.…”
Section: Introductionmentioning
confidence: 99%